2022
DOI: 10.1177/13591053221134740
|View full text |Cite
|
Sign up to set email alerts
|

Living with Parkinson’s disease: A qualitative study of spousal perspectives

Abstract: Research has demonstrated that Parkinson’s disease can have adverse psychological effects on caregivers. Very few studies have focused on the experiences of spouses who are not primary caregivers or who do not identify as primary caregivers. The aim of this study was to explore the experiences of spouses who are not primary caregivers or do not identify as primary caregivers. Twelve Israeli women, spouses of men with Parkinson’s disease, were interviewed using a semi-structured in-depth approach. Thematic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This led an Israeli research team to investigate the experiences of spouses who do not identify as primary caregivers. 1 They found that the progressive nature of PD led to a dynamic nature to the participants' experiences; as the disease progressed, it intensified in their experience. In a similar fashion to the 'on-off' phenomenon experienced by levodopatreated PD patients, where patients go through cycles of fluctuating symptoms, spouses experienced a 'seesaw' dynamic where the disease took up more (off) or less (on) space in their lives.…”
mentioning
confidence: 99%
“…This led an Israeli research team to investigate the experiences of spouses who do not identify as primary caregivers. 1 They found that the progressive nature of PD led to a dynamic nature to the participants' experiences; as the disease progressed, it intensified in their experience. In a similar fashion to the 'on-off' phenomenon experienced by levodopatreated PD patients, where patients go through cycles of fluctuating symptoms, spouses experienced a 'seesaw' dynamic where the disease took up more (off) or less (on) space in their lives.…”
mentioning
confidence: 99%